An empirical study of workforce diversity in small and medium firms in the Arabian Gulf: the Omani case. (1st November 2007) - Yusuf, Attahir
The study explores workforce diversity in "under-studied" Arabian Gulf. Specifically, it investigates what Small and Medium Enterprises (SMEs) are doing right with respect to workforce diversity and what they are not doing right. It also studies the relationship between motivation to diversify, level of education, gender, indigenous-ship, and level of workforce diversification in SMEs. The result indicates that the organisations are doing much good towards diversification than otherwise. There is also a positive and significant relationship between education and indigence and the level of workforce diversification in the SME sector.